2018
DOI: 10.1177/0959683618782607
|View full text |Cite|
|
Sign up to set email alerts
|

Validating a continental European charcoal calibration dataset

Abstract: Large-scale training sets enabling quantitative reconstructions of past fire parameters are needed to better assess potential effects of increased fire hazard under global warming conditions. The aim of this article is to validate recently developed continental regression equations for the reconstruction of fire number, intensity and size. These transfer functions were built by linking satellite data and charcoal collected in annually sampled sediment traps. We apply these European regression equations to four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Some studies have attempted to linearly link charcoal number with local fire characteristics such as burned area and fire occurrence. No significant relationship has been found within grassland ecosystems (Duffin et al, 2008; Leys et al, 2015), but charcoal number has been shown to be linearly correlated with more regional events (Adolf et al, 2018; Asselin and Payette, 2005). Using the variable classification, we found that no local variables (within the smallest zone) explained the median surface area of charcoal particles but only semi-regional (15-km zone) and regional (30-km zone) scale variables.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Some studies have attempted to linearly link charcoal number with local fire characteristics such as burned area and fire occurrence. No significant relationship has been found within grassland ecosystems (Duffin et al, 2008; Leys et al, 2015), but charcoal number has been shown to be linearly correlated with more regional events (Adolf et al, 2018; Asselin and Payette, 2005). Using the variable classification, we found that no local variables (within the smallest zone) explained the median surface area of charcoal particles but only semi-regional (15-km zone) and regional (30-km zone) scale variables.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, low severity fires produce few charred particles relative to burned biomass, and the energy released by the fire front is too low to allow their suspension and thus their transportation away from the burned area (Ohlson and Tryterud, 2000). Studies have only considered burned area or fire occurrence when investigating the role of components on charcoal measurements (Adolf et al, 2018; Leys et al, 2015). The present study thus highlights the importance of fire severity in understanding the charcoal time series (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linking the charcoal influx values to MODIS-inferred modern day burning regimes, an approach used by Adolf et al (2018b), showed that the source area for macroscopic and microscopic charcoal is estimated to be 16 km for macroscopic charcoal and 180 km for microscopic charcoal, assuming that distance is indicated by the strongest correlations between charcoal and satellite data (Fig. 6).…”
Section: Charcoal Area Validationmentioning
confidence: 99%
“…The size of the source area for macroscopic charcoal and microscopic charcoal into a depositional environment is contentious. Macroscopic charcoal is widely suggested to reflect burning from a local to sub-regional source area between 0 and 10 km radius (Gavin et al 2003;Lynch et al 2004;Petersn and Higuera 2007;Higuera et al 2007Higuera et al , 2011Anderson and Wahl 2016), while microscopic charcoal is suggested to primarily reflect regional burning within a radius of up to several hundred kilometres (Clark 1988); however, recent validation of charcoal dispersal across Europe linked both macroscopic and microscopic charcoal influx to a regional source area of around 40 km radius (Adolf et al 2018b). Our results from Cenote Kail indicate that the catchment area for macroscopic charcoal and microscopic charcoal varied by a degree of magnitude.…”
Section: What Is Cenote Kail's Charcoal Source Area?mentioning
confidence: 99%